2021
DOI: 10.1155/2021/2866475
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNA Regulatory Networks and Candidate Markers for Fracture Healing in Mice

Abstract: Background. It is important to improve the understanding of the fracture healing process at the molecular levels, then to discover potential miRNA regulatory mechanisms and candidate markers. Methods. Expression profiles of mRNA and miRNA were obtained from the Gene Expression Omnibus database. We performed differential analysis, enrichment analysis, protein-protein interaction (PPI) network analysis. The miRNA-mRNA network analysis was also performed. Results. We identified 499 differentially expressed mRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Inhibitory miRNAs can inhibit osteoblast CP and promote CA by targeting osteogenic genes in vitro [7,8]. For example, increased miR-221-3p expression during bone healing in diabetic fracture patients can lead to impaired endochondral ossification and reduced bone remodeling [9].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory miRNAs can inhibit osteoblast CP and promote CA by targeting osteogenic genes in vitro [7,8]. For example, increased miR-221-3p expression during bone healing in diabetic fracture patients can lead to impaired endochondral ossification and reduced bone remodeling [9].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma miR-92a plays an important role in human fracture healing, and its inhibition promotes fracture healing through angiogenesis ( Murata et al, 2014 ). It has also been shown that the miRNA–mRNA network has a regulatory role in osteoblast differentiation, the pathogenesis of osteoporosis, and fracture healing ( An et al, 2014 ; Zhang et al, 2020 ; Li et al, 2021 ; Mohanapriya et al, 2022 ). Based on the advantages of miRNA, transcriptome analysis combining miRNA and mRNA of fractures will help to identify potential therapeutic targets for fracture healing.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma miR-92a plays an important role in human fracture healing, and its inhibition promotes fracture healing through angiogenesis (Murata et al, 2014). It has also been shown that the miRNA-mRNA network has a regulatory role in osteoblast differentiation, the pathogenesis of osteoporosis, and fracture healing (An et al, 2014;Zhang et al, 2020;Li et al, 2021;Mohanapriya et al, 2022). Based on the advantages of miRNA, transcriptome analysis combining miRNA and mRNA of fractures will help to identify potential therapeutic targets for fracture healing.…”
Section: Introductionmentioning
confidence: 99%